Penggunaan Lagu Dalam Pembelajaran Simple Presen Tense Untuk Meningkatkan Kemampuan Bahasa Inggris di Lingkungan XVIII, Kelurahan Binjai, Kecamatan Medan Denai, Kabupaten Kota Medan - Kresna Ningsih Manik; Merry Susanty Br Tarigan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2022)
This program took place from February 21 to 23, 2022, in the XVIII neighborhood, Binjai Village, Denai District, Medan Regency/City, North Sumatra Province. The program is designed for children aged 8-12, and the materials taught include Simple Present Tense and several songs that utilize Simple Present Tense. The duration of each session is 90 minutes. The number of children involved is approximately ten (10) individuals. Each session is divided into two parts, the first 45 minutes facilitated by Teacher A, and the remaining 45 minutes continued by Teacher B, and so on until the third day. Upon completion of this program, the children showed significant improvement in listening skills, vocabulary recall, and vocabulary memorization, as reflected in the test scores given by the instructors before and after the program. Learning through English songs has proven to be highly effective for children in the XVIII neighborhood, Binjai Village, Denai District. The use of songs as a teaching method helps enhance listening abilities, learn new vocabulary, develop speaking skills, and improve social skills in children. Therefore, incorporating songs into early English language learning is highly recommended.